1998
DOI: 10.1101/gad.12.1.107
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor gene Smad4/Dpc4 is required for gastrulation and later for anterior development of the mouse embryo

Abstract: Mutations in the SMAD4/DPC4 tumor suppressor gene, a key signal transducer in most TGF␤-related pathways, are involved in 50% of pancreatic cancers. Homozygous Smad4 mutant mice die before day 7.5 of embryogenesis. Mutant embryos have reduced size, fail to gastrulate or express a mesodermal marker, and show abnormal visceral endoderm development. Growth retardation of the Smad4-deficient embryos results from reduced cell proliferation rather than increased apoptosis. Aggregation of mutant Smad4 ES cells with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
325
0
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 458 publications
(353 citation statements)
references
References 56 publications
14
325
0
5
Order By: Relevance
“…Mouse embryos deficient in Smad4 display defective epiblast proliferation and delayed outgrowth of the inner cell mass [13], and mice lacking ALK-3 bone morphogenetic protein (BMP) type IA receptor) exhibit reduced cell proliferation in the epiblast [14], demonstrating that BMP signaling plays important roles in the maintenance of mouse ES cell identity. Qi et al [15] reported that BMP-4 provided by feeder cells is necessary for the maintenance of ES cell self-renewal, and that effect of BMP-4 is accomplished by means of inhibition of both extracellular receptor kinase (ERK) and p38 mitogen-activated protein kinase (MAPK) pathways.…”
Section: Tgf-β Family Signaling In the Maintenance Of Pluripotency Anmentioning
confidence: 99%
“…Mouse embryos deficient in Smad4 display defective epiblast proliferation and delayed outgrowth of the inner cell mass [13], and mice lacking ALK-3 bone morphogenetic protein (BMP) type IA receptor) exhibit reduced cell proliferation in the epiblast [14], demonstrating that BMP signaling plays important roles in the maintenance of mouse ES cell identity. Qi et al [15] reported that BMP-4 provided by feeder cells is necessary for the maintenance of ES cell self-renewal, and that effect of BMP-4 is accomplished by means of inhibition of both extracellular receptor kinase (ERK) and p38 mitogen-activated protein kinase (MAPK) pathways.…”
Section: Tgf-β Family Signaling In the Maintenance Of Pluripotency Anmentioning
confidence: 99%
“…Smad4 knock-out mice die between E7.5 and E8.5, and show growth retardation, no mesoderm formation, no gastrulation, and abnormal visceral endoderm development. The gastrulation defect of Smad4 null mice was rescued when a mutant embryos were surrounded by wild-type extraembryonic tissue (Sirard et al, 1998;Yang et al, 1998). Heterozygous Smad4 mice survive and develop malignant intestinal tumors after 1 year of age (Takaku et al, 1999;, most likely due to a loss of heterozygosity and reduplication of the mutated Smad4 allele (Takaku et al, 1999).…”
Section: Smad Knock-out Micementioning
confidence: 99%
“…In mice, inactivation of the Smad4 gene leads to embryonic lethality. Heterozygous mice do not display a cancer phenotype up to 1 year of age (Sirard et al, 1998). If a Smad4 mutation is combined with an Apc mutation, it was shown that the progression was enhanced and the endpoint of tumorigenesis was more malignant (Takaku et al, 1998).…”
Section: Mouse Models For Hnpccmentioning
confidence: 99%